Moral distress experienced by online suicide prevention volunteers - Shuxian, Liu; Mei, Sun; Siyuan, Tang (Acta Bioethica, 2022)
Background: With the increasing number of internet users, it becomes feasible to identify individuals at high risk of suicide and then carry out online suicide prevention. At the same time, online suicide prevention volunteers may encounter moral distress, which requires more attention. Purpose: This study aimed to explore the experience of moral distress in online suicide prevention. Method: The study was carried out as a qualitative study following the method of phenomenology. 11 interviewers were recruited through the purposive sampling method. Data were collected through semi-structured, in-depth face-to-face interviews. Colaizzi’s phenomenological framework was used for data analysis. Results: All participants reported they encountered moral distress during online suicide prevention. Four themes were condensed, including: “constraints from the surrounding,” “be cruel to be kind,” “baby spoiled by free milk,” and “when face death and depression” Participants also described their emotional experiences and response when they encountered moral distress. Conclusion: Moral distress in the process of online suicide prevention exists. More attention should be paid to the moral distress and ethical issues in online suicide prevention as the internet gradually becomes a brand-new way to prevent suicide.